(untitled) (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2016)
In this paper an attempt has been made to contextualize the ecological dimension of contemporary Catholic social teaching. With this aim in mind, the authors discuss the merits of several theories and approaches (political economy approaches, ecological modernization theory, environmental justice theory, and social constructionism) coming from environmental sociology and other disciplinary traditions in the social sciences. After an analysis of relevant historical documents of Catholic social teaching with respect to the environmental issues covered by them, the authors discuss the main lines of argument present in the recent (2015) encyclical Laudato Si’ (Pope Francis) and interpret them in the aforementioned theoretical framework. In conclusion, the usefulness of Catholic social teaching for the public dialogue between science and other relevant stakeholders, as well as its main strengths and weaknesses have been discussed. Keywords: Catholic social teaching, Laudato Si’, environmental sociology, development, environment, ecological crisis